Introduction to Financial Futures and Options - Redhead Keith; Woodhead-Faulkner (1990)
A practical introduction to the subject, which assumes no previous knowledge but which nevertheless takes the reader to a reasonably high level of sophistication. Preface, Introduction, Currency Futures, Short-Term Interest Rate Futures, Long-Term Interest Rate Futures, Stock Index Futures, Hedging with Options, Trading with Options, Arbitrage with Options, Derivatives in Portfolio Management, Taxation, Outlook for the Future, Appendices, The Role of Stock Index Futures in the Stock Market Crash of October 1987, The Black-Scholes Option Pricing Model, Delta and Gamma and Kappa, Glossary, Index.